Development, characterization and anti-diabetic properties of thymoquinone rich fraction nanoemulsion obtained from black cumin - Tubesha, Zaki A.H. (2013)
For thousands of years, natural products have played important roles throughout the world in preventing and treating human diseases. Black cumin (Nigella sativa L.) and its bioactive constituents, thymoquinone (TQ), have been used for various health benefits such as antidiabetic, antitumor, antihypertensive, antioxidative and antibacterial agents. Type 2 diabetes mellitus (T2DM) which accounts for over 90 % of diabetes cases is currently a major chronic disease affecting about 6 % of the global population. Therefore, discovering new therapies is vital for management of T2DM. Although TQ and thymoquinone rich fraction (TQRF) are known to be powerful antioxidants and have hypoglycemic properties, their administration in vivo remains problematic partly due to their low bioavailability. Lipid nanoemulsions from some medicinal plant oils such as TQRF or from hydrophobic bioactives such as TQ are attractive candidates for improving solubility and bioavailability of the oils and their bioactives. Therefore, the aim of the present study was to develop, characterize, and investigate antidiabetic properties of TQRF nanoemulsion (TQRFNE) and TQ nanoemulsion (TQNE). Conventional emulsions from TQRF (TQRFCE) and from TQ (TQCE) were also prepared for comparison. TQRF extracted from N. sativa using supercritical fluid extraction (SFE) contained 4.45 % TQ and was used to develop TQRFNE and TQRFCE. To develop TQNE and TQCE, Triolein (TR) was used as a carrier of commercially acquired TQ based on the concentration of TQ in TQRF. Conventional emulsions were prepared first by mixing 5 % lipid phase (TQRF or TR which contains calculated amount of TQ) with 95 % aqueous phase (2 % Tween-80, and 93 % distilled water) at room temperature using Ultra-Turrax mixer (13000 rpm / 3 min). Nanoemulsions were produced by passing the conventional emulsions through high pressure Homogenizer (800 bars and five homogenization cycles). In the characterization study, the changes in particle size, zeta potential,polydispersity index, refractive index, and chemical stability (loss of TQ during storage) of all emulsions were investigated over a period of 6 months at three different storage temperatures (4, 25, and 40 ˚C). At the end of characterization period, all nanoemulsions displayed good physical and chemical stability; there was no phase separation or any sign of instability of all nanoemulsion samples. In the antioxidant study, all emulsion samples were tested for antioxidant activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH•), 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS•+), and β-carotene bleaching (BCB) assays using UV- visible spectrophotometer, and hydroxyl radical scavenging activity by electron spin resonance (ESR) spectrometer. Antioxidant activities of all nanoemulsions were slightly lower compared to conventional emulsions. In addition, acute toxicity of TQRFNE, and TQNE was studied using Sprague–Dawley rats. All the parameters measured were unaffected as compared to the negative control group (administered with distilled water). Further study was done to investigate the antidiabetic properties of the emulsions using T2DM animal model. Rats treated with TQRFNE and TQNE (10 ml/kg bw) exhibited a significant (P < 0.05) reduction in plasma total cholesterol levels (43 and 58 %), triglyceride (45 and 59 %), and fasting plasma glucose (42.1 and 54.9 %), respectively, compared to diabetic rats (DC group). However, TQRFCE and TQCE (10 ml/kg bw) also exhibited a significant (P < 0.05) reduction in plasma total cholesterol levels (56 and 69 %), triglyceride (57 and 67 %), and fasting plasma glucose (58 and 54.2 %), respectively, compared to DC group. For the liver and kidney function tests, the concentration of Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), Aspartate aminotransferase (AST), Urea (URE), and Creatinine (CREA) were also measured to test any toxic effect on all tested groups. All tested parameters were also significantly lower compared to DC group. For the gene expression study, genes related to glucose metabolism (FBP1), cholesterol metabolism (LDL-R) and antioxidants (SOD1) were evaluated in this study. Treatment with TQRFNE showed antihyperglycemic,hypocholesterolemic and antioxidant effects, partly through regulation of above mentioned genes. Taken together, our finding showed that TQRFNE as a novel nanocarrier has the potential to produce better metabolic outcomes in T2DM. In addition, the findings also suggest that TQRFNE may be better than metformin in management of T2DM, and that it potentially could improve the wellbeing of diabetics through better control of metabolic indices, and likely fewer side effects.